2015
DOI: 10.1007/s40265-015-0441-7
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase Clostridium Histolyticum: A Review in Peyronie’s Disease

Abstract: Collagenase Clostridium Histolyticum (CCH) (Xiaflex(®), Xiapex(®)) intralesional injection is a mixture of class I (AUX-I) and class II (AUX-II) clostridial collagenases. It is indicated for the treatment of adult men with Peyronie's disease with a palpable plaque and curvature deformity of ≥ 30° at the start of therapy. This article reviews the efficacy and tolerability of CCH in this indication and briefly summarizes its pharmacology. CCH treatment significantly improved penile curvature deformity and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…26 These enzymes manifest their effects through hydrolysis of types I and III collagen fibers (found in bone, connective tissue, scar, and PD plaques) while sparing collagen type IV (found in vascular and nervous tissues). 2226 Ex vivo studies have confirmed that each form of collagenase cleaves collagen fibers at a different site, leading to the synergistic effect of CCH. 25…”
Section: Collagenase Clostridium Histolyticummentioning
confidence: 98%
See 2 more Smart Citations
“…26 These enzymes manifest their effects through hydrolysis of types I and III collagen fibers (found in bone, connective tissue, scar, and PD plaques) while sparing collagen type IV (found in vascular and nervous tissues). 2226 Ex vivo studies have confirmed that each form of collagenase cleaves collagen fibers at a different site, leading to the synergistic effect of CCH. 25…”
Section: Collagenase Clostridium Histolyticummentioning
confidence: 98%
“…2226 Ex vivo studies have confirmed that each form of collagenase cleaves collagen fibers at a different site, leading to the synergistic effect of CCH. 25…”
Section: Collagenase Clostridium Histolyticummentioning
confidence: 98%
See 1 more Smart Citation
“…The prevalence of PD is reportedly from 22.4 to 25.7 per 100,000 men, and the average age of patients is 55 years (Herati and Pastuszak, 2016). Actually, the incidence of PD might be underestimated due to under-reporting bias from those patients who are reluctant to visit hospitals (Dhillon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of PD is reportedly from 22.4 to 25.7 per 100,000 men, and the average age of patients is 55 years ( Herati and Pastuszak, 2016 ). Actually, the incidence of PD might be underestimated due to under-reporting bias from those patients who are reluctant to visit hospitals ( Dhillon, 2015 ). As of yet, surgery is considered the gold-standard treatment of PD in the stable phase to provide patients with permanent functional recovery and correction of penile deformity ( Wymer et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%